The genetic interactions between non-alcoholic fatty liver disease and cardiovascular diseases - Chew, Nicholas W.S.; Chong, Bryan; Ng, Cheng Han; Kong, Gwyneth; Chin, Yip Han; Xiao, Wang; Lee, Mick; Dan, Yock Young; Muthiah, Mark D.; Foo, Roger (Frontiers in Genetics, 2022)
The ongoing debate on whether non-alcoholic fatty liver disease (NAFLD) is an active contributor or an innocent bystander in the development of cardiovascular disease (CVD) has sparked interests in understanding the common mediators between the two biologically distinct entities. This comprehensive review identifies and curates genetic studies of NAFLD overlapping with CVD, and describes the colinear as well as opposing correlations between genetic associations for the two diseases. Here, CVD described in relation to NAFLD are coronary artery disease, cardiomyopathy and atrial fibrillation. Unique findings of this review included certain NAFLD susceptibility genes that possessed cardioprotective properties. Moreover, the complex interactions of genetic and environmental risk factors shed light on the disparity in genetic influence on NAFLD and its incident CVD. This serves to unravel NAFLD-mediated pathways in order to reduce CVD events, and helps identify targeted treatment strategies, develop polygenic risk scores to improve risk prediction and personalise disease prevention.